A [C1 + C2] route to propargylidyne complexes. Issue 19 (24th April 2019) - Hill, Anthony F.; Manzano, Richard A.
Abstract : The reactions of [W(CBr)(CO)2 (Tp*)] with a range of terminal alkynes (RCCH), mediated by [Pd(PPh3 )4 ] and CuI, afford new propargylidynes [W(C–CCR)(CO)2 (Tp*)] [R = t Bu, C6 H4 X (X = H, NH2, NO2 ), APh3 (A = C, Si, Ge), B(O2 CCH2 )2 NMe]. Abstract : The reactions of [W(CBr)(CO)2 (Tp*)] (Tp* = hydrotris(dimethylpyrazolyl)borate) with a range of terminal alkynes (RCCH), mediated by [Pd(PPh3 )4 ] and CuI, afford new proparylidynes [W(C–CCR)(CO)2 (Tp*)] [R = t Bu, C6 H4 X (X = H, NH2, NO2 ), ferrocenyl, APh3 (A = C, Si, Ge), B(O2 CCH2 )2 NMe]. Similar treatment of [W(CBr)(CO)2 (Tp*)] with Ph2 Si(CCH)2 affords the ditungstaoctatetrayne [W2 (μ-C6 )(CO)4 (Tp*)2 ] while the bimetallic complex [W2 {μ-(CCC)2 SiPh2 }(CO)4 (Tp*)2 ], which is obtained from [W(CBr)(CO)2 (Tp*)] and Ph2 Si(CCSnPh3 )2, reacts with [AuCl(THT)] (THT = tetrahydrothiophene) to provide the tetrametallic complex [W2 Au2 {μ-(CCC)2 SiPh2 }Cl2 (CO)4 (Tp*)2 ].